Optimization of the Solubility of HIV-1-Neutralizing Antibody 10E8 through Somatic Variation and Structure-Based Design - Kwon, Young D. (J Virol, 2016)
Extraordinary antibodies capable of near pan-neutralization of HIV-1 have been identified. One of the broadest is antibody 10E8, which recognizes the membrane-proximal external region (MPER) of the HIV-1 envelope and neutralizes >95% of circulating HIV-1 strains. If delivered passively, 10E8 might serve to prevent or treat HIV-1 infection. Antibody 10E8, however, is markedly less soluble than other antibodies. Here, we describe the use of both structural biology and somatic variation to develop optimized versions of 10E8 with increased solubility. From the structure of 10E8, we identified a prominent hydrophobic patch; reversion of four hydrophobic residues in this patch to their hydrophilic germ line counterparts resulted in an ∼10-fold decrease in turbidity. We also used somatic variants of 10E8, identified previously by next-generation sequencing, to optimize heavy and light chains; this process yielded several improved variants. Of these, variant 10E8v4 with 26 changes versus the parent 10E8 was the most soluble, with a paratope we showed crystallographically to be virtually identical to that of 10E8, a potency on a panel of 200 HIV-1 isolates also similar to that of 10E8, and a half-life in rhesus macaques of ∼10 days. An anomaly in 10E8v4 size exclusion chromatography that appeared to be related to conformational isomerization was resolved by engineering an interchain disulfide. Thus, by combining a structure-based approach with natural variation in potency and solubility from the 10E8 lineage, we successfully created variants of 10E8 which retained the potency and extraordinary neutralization breadth of the parent 10E8 but with substantially increased solubility. IMPORTANCE Antibody 10E8 could be used to prevent HIV-1 infection, if manufactured and delivered economically. It suffers, however, from issues of solubility, which impede manufacturing. We hypothesized that the physical characteristic of 10E8 could be improved through rational design, without compromising breadth and potency. We used structural biology to identify hydrophobic patches on 10E8, which did not appear to be involved in 10E8 function. Reversion of hydrophobic residues in these patches to their hydrophilic germ line counterparts increased solubility. Next, clues from somatic variants of 10E8, identified by next-generation sequencing, were incorporated. A combination of structure-based design and somatic variant optimization led to 10E8v4, with substantially improved solubility and similar potency compared to the parent 10E8. The cocrystal structure of antibody 10E8v4 with its HIV-1 epitope was highly similar to that with the parent 10E8, despite 26 alterations in sequence and substantially improved solubility. Antibody 10E8v4 may be suitable for manufacturing.